DEVELOPMENT OF IPAS INTERACTIVE LEARNING MEDIA USING AUGMENTED REALITY TO IMPROVE THE UNDERSTANDING OF GRADE V ELEMENTARY SCHOOL STUDENTS - Zada Talitha Ramdhani; Ana Andriani (SOSIOEDUKASI, 2026)
The low level of students’ understanding of the Human Respiratory System material and the limited availability of learning media capable of visualizing abstract respiratory organs form the background of this study. The objectives of this research are: (1) to develop an Augmented Reality (AR)-based science learning media on the human respiratory system material; (2) to analyze the validity of the AR-based learning media; (3) to examine the practicality of the AR-based learning media; (4) to test the effectiveness of the AR-based learning media in improving students’ learning outcomes; and (5) to analyze the differences in learning outcomes between the use of AR-based media and expository learning. The method used was Research and Development (R&D) with the ADDIE model comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 26 experimental class students and 28 control class students. Data collection techniques included observation, interviews, questionnaires, expert validation, and learning outcome tests (pretest and posttest). Data analysis used descriptive statistics, N-Gain Score analysis, and the Mann-Whitney U Test. Data validity was ensured through source triangulation. Results showed media expert validation of 4.8 (Very Good) and content expert validation of 4.6 (Very Good); teacher response 4.6 (Very Good) and student response 3.45 (Very Good). The experimental class mean posttest score (90.65) exceeded the control class (87.93). N-Gain Score analysis showed that the experimental class mean N-Gain of 75.53 (High category) exceeded the control class mean of 57.12 (Medium category), demonstrating that the interactive AR-based IPAS learning media is more effective in improving student understanding